EDUCATION TRANSFORMATION: THE IMPACT OF TEACHER TRAINING IN IMPLEMENTING THE MERDEKA CURRICULUM IN MADRASAH IBTIDAIYAH - Taufik, Imam; Rindanigsih, Ida (Antis-Publisher, 2024)
The Merdeka Curriculum is an important milestone in the transformation of education in madrasah ibtidaiyah, encouraging the need to improve the quality of teachers through directed training. The background of the adoption of the Merdeka Curriculum lies in changing the learning paradigm towards an inclusive approach, integrating national values without setting aside the substance of religious education. The purpose of this study is to describe the impact of teacher training on the implementation of Merdeka Curriculum in madrasah ibtidaiyah. This research method uses a literature study approach and analyzes various sources relevant to the context of teacher training and the adoption of Merdeka Curriculum in madrasah. In this study, it is presented that teacher training has a significant impact. Teachers who receive directed training are able to better apply Merdeka Curriculum concepts, improve teaching quality, and create a more dynamic learning environment. The results show that teacher training directly contributes to improving their understanding of the Merdeka Curriculum concept, improving skills in designing lessons that are in line with the demands of the new curriculum, and having a positive impact on student achievement. Improved learning quality, collaboration between teachers, and readiness to deal with change are the visible results of investing in teacher training in the context of Merdeka Curriculum in madrasah ibtidaiyah. This confirms that teacher training is not only a necessity, but also a necessity in realizing adaptive and inclusive education.